1996
DOI: 10.1128/jcm.34.12.3120-3128.1996
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic DNA sequences in patients with chronic idiopathic prostatitis

Abstract: Half of all men experience symptoms of prostatitis at some time in their lives, but the etiology is unknown for more than 90% of patients. Optimal clinical and culture methods were used to select 135 men with chronic prostatitis refractory to multiple previous courses of antimicrobial therapy. The subjects had no evidence of structural or functional lower genitourinary tract abnormalities of bacteriuria or bacterial prostatitis by traditional clinical tests, or of urethritis or urethral pathogens by culture. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(51 citation statements)
references
References 50 publications
1
47
1
2
Order By: Relevance
“…A large study of 597 prostatitis patients indicated that nearly one-third were diagnosed with prostatodynia, which is a significant fraction of the urological population (10). The recent literature suggests that the condition referred to as chronic idiopathic (nonbacterial) prostatitis may actually have an infectious etiology (18,32,38,53). Some patients relate the onset of their symptoms to sexual activity-sometimes associated with acute urethritis (7)-while others have indicated no relationship with sexual activity.…”
Section: Definition Of a Problemmentioning
confidence: 99%
“…A large study of 597 prostatitis patients indicated that nearly one-third were diagnosed with prostatodynia, which is a significant fraction of the urological population (10). The recent literature suggests that the condition referred to as chronic idiopathic (nonbacterial) prostatitis may actually have an infectious etiology (18,32,38,53). Some patients relate the onset of their symptoms to sexual activity-sometimes associated with acute urethritis (7)-while others have indicated no relationship with sexual activity.…”
Section: Definition Of a Problemmentioning
confidence: 99%
“…Ureaplasma was not identified. However, DNA sequences common to a range of bacteria were found 6 . The significance of these non‐culturable micro‐organisms is uncertain, because similar findings were subsequently reported in men without prostatitis.…”
Section: Aetiology and Pathogenesismentioning
confidence: 87%
“…7. Intra-and extracellularly growing, fastidious infectious agents can be detected in cell scrapings and biopsies by culture, light and electron microscopy, or molecular biological techniques, i.e., hybridization or polymerase chain reactions (Murray et al, 1995;Krieger et al, 1996).…”
Section: Methodsmentioning
confidence: 99%